Death of the triple arthrodesis?. Issue 5 (October 2015) - Walker, Roland; Francis, Randhir; Singh, Sam; Ajuied, Adil
Abstract: Triple arthrodesis has for many years been a gold-standard treatment for a multitude of hindfoot deformities and arthritis since it was first described in 1923 by Edwin W. Ryerson of Chicago (1872–1961). However, in contemporary foot and ankle practice there has been a shift toward joint preserving techniques. In this article we cover the biomechanics of the triple joint and the surgical technique for a standard two-incision approach. The role of this once common procedure in modern foot and ankle practice is assessed by a systematic review of the literature reporting series of triple arthrodesis over the past 10 years. 13 studies met the inclusion criteria and reported the results of 515 operations in 481 patients. The three most common diagnoses were tibialis posterior insufficiency (30%), inflammatory arthropathy (19%) and neuromuscular disorders (18%). Subjective outcome was good in 75%, fair in 18% and poor in 7.9% (n = 354). The complication rate was relatively high, with wound complications and/or infections in approximately 10% and non-union of at least one joint in 6.5%. There have been recent advances in surgical technique. It is possible to perform triple arthrodesis through a single medial incision and a double arthrodesis (subtalar and talonavicular joint) via a medial approach is currently emerging as a good alternative for the plano-valgus foot. External fixation can be useful for gradual correction of severe deformity and surgeons have started using arthroscopic techniques with early success. In conclusion, the triple arthrodesis is still alive and remains a useful operation for the foot and ankle surgeon. However, trainees should be aware of the alternatives and aim to preserve healthy joints where possible.